2018
DOI: 10.1108/jocm-06-2017-0236
|View full text |Cite
|
Sign up to set email alerts
|

Tacit and explicit knowledge management and assessment of quality performance of public R&D in emerging economies

Abstract: Purpose The authors investigate the relationship between the structure and the functioning of scientific and technical (S&T) personnel and the quality research and development (R&D) performance output of laboratories functioning under the Council of Scientific and Industrial Research (CSIR), India. The purpose of this paper is to examine how rapid economic and social changes and the demand for better accountability are addressed by public R&D institutions in a specific developing economy. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…Innovation and knowledge are becoming vital for cities, firms, regions, and countries to maintain competitive advantages and sustainable development (Gui et al., 2018). Urban developers have applied knowledge and scenario programming to investigate current decisions' upcoming results, particularly when there are doubts and diverse shareholder values (Chakraborty & McMillan, 2015; Roy & Mitra, 2018). The knowledge domain of planning includes technological, social, economic, political systems, and environments constantly evolving rapid expansion (Duarte Alonso et al., 2019).…”
Section: Model and Methodologymentioning
confidence: 99%
“…Innovation and knowledge are becoming vital for cities, firms, regions, and countries to maintain competitive advantages and sustainable development (Gui et al., 2018). Urban developers have applied knowledge and scenario programming to investigate current decisions' upcoming results, particularly when there are doubts and diverse shareholder values (Chakraborty & McMillan, 2015; Roy & Mitra, 2018). The knowledge domain of planning includes technological, social, economic, political systems, and environments constantly evolving rapid expansion (Duarte Alonso et al., 2019).…”
Section: Model and Methodologymentioning
confidence: 99%
“…(2) Knowledge storage and dissemination. Explicit orientation emphasizes knowledge coding, diverse forms of documents that store and transmit knowledge, helping employees acquire and share knowledge [33]. Tacit orientation emphasizes interpersonal communication which increases the dissemination of knowledge through social networks via social media [34].…”
Section: Framework Of Km Strategymentioning
confidence: 99%
“…This study also found that when more proprietary knowledge and information can be shared, such as know-how, and other events that might affect other parties in the supply chains, manufacturers can enrich their innovation activities, identify new aspects to meet customer expectation and reduce risks in their innovation activities. Through communication, SKD helps manufacturers reconfiguring a new type of knowledge that can enhance significantly the quality and innovation performance (Roy & Mitra, 2018). Supplier knowledge development plays a significant role as 'business intelligence' in closing the gaps through organisational boundaries.…”
Section: Discussion and Implicationmentioning
confidence: 99%